Smoking, Haemostatic Factors and the Severity of Aorto-lliac and Femoro-Popliteal Disease - Smith, F B; Lee, A J; Fowkes, F G R; Rumley, A; Lowe, G D O (Thrombosis and Haemostasis, 1996)
To determine relationships between haemostatic and rheological factors and severity of peripheral atherosclerosis and differences by site, an angiographic cross-sectional survey was carried out on 192 men and women with intermittent claudication or rest pain. 34 patients were classified as having aorto-iliac disease, 85 femoro-popliteal disease and 73 dual-site disease. Mean levels of haemostatic or rheological factors did not differ significantly between the three site groups. In all 192 patients, disease severity in the femoro-popliteal segments was correlated with plasma nephelometric fibrinogen (r = 0.20, p ≤0.01), von Willebrand factor (r = 0.14, p ≤0.05) and fibrin D-dimer (r = 0.22, p ≤0.001). On multiple regression analyses, fibrinogen was independently associated with disease severity in the femoro-popliteal segments (p ≤0.05), but not in the aorto-iliac segments. Adjustment for packyears or serum thiocyanate had little effect on the association of fibrinogen with severity of disease. An inverse relationship between plasminogen activator inhibitor and disease severity in the femoro-popliteal segments was found only in men (r = -0.24, p ≤0.01). We conclude that elevated fibrinogen and disturbed fibrinolytic activity may be related to the extent of disease within the femoro-popliteal arteries, more so than in the aorto-iliac arteries.